A biomimetic lipid library for gene delivery through thiol-yne click chemistry - Li, Linxian; Zahner, David; Levkin, Pavel (Biomaterials, 2012)
The delivery of nucleic acids such as plasmid DNA and siRNA into cells is a cornerstone of biological research and is of fundamental importance for medical therapeutics. Although most gene delivery therapeutics in clinical trials are based on viral vectors, safety issues remain a major concern. Non-viral vectors, such as cationic lipids and polymers, offer safer alternatives but their gene delivery efficiencies are usually not high enough for clinical applications. Thus, there is a high demand for more efficient and safe non-viral vectors. Here, we present a facile two-step method based on thiol-yne click chemistry for parallel synthesis of libraries of new biomimetic cationic thioether lipids. A library of novel lipids was synthesized using the developed method and more than 10% of the lipids showed highly efficient transfection in different cell types, surpassing the efficiency of several popular commercial transfection reagents. One of the new lipids showed highly efficient siRNA delivery to multiple cell types and could successfully deliver DNA plasmid to difficult-to-transfect mouse embryonic stem cells (mESC). Analysis of structure–activity relationship revealed that the length of the hydrophobic alkyl groups was a key parameter for efficient cell transfection and was more important for transfection efficiency than the nature of cationic head groups. The correlation of the size and surface charge of liposomes with transfection efficiency is described.